Intracerebral Hemorrhage in Multiple Sclerosis: Disease Evolution or Treatment-Related Complication?: A Case Report - Semnic, Isidora; Bonifacic, David; Vuletic, Vladimira (Brazilian Journal of Case Reports, 2026)
Intracerebral hemorrhage (ICH) is an uncommon but clinically significant event in patients with multiple sclerosis (MS), and its relationship to disease-modifying therapies (DMTs) remains incompletely understood. We report the case of a patient with long-standing MS who developed an ICH. The patient had a 16-year history of MS and was reluctant towards long-term DMT. Cladribine was introduced as a high-efficacy treatment, and less than two years after treatment initiation, the patient experienced a spontaneous ICH. Despite the hemorrhagic event, cladribine therapy was continued, resulting in subsequent stabilization of MS disease activity, with only mild residual neurological deficit. A thorough evaluation revealed no alternative secondary causes neither conventional risk factors for the hemorrhage. Although current literature does not establish a definitive link between cladribine and ICH, the temporal relationship in this case enhances the possibility of a therapy-related contribution. Given the absence of definitive causal evidence, we propose that chronic neuroinflammation with impaired cerebrovascular autoregulation, compounded by therapy-induced immunosuppression, could contribute to the event. However, causality cannot be inferred from the single observation of disease versus treatment-related factors. Further data are needed to clarify hemorrhagic risk in MS patients receiving DMT and the need for continued pharmacovigilance when using high-efficacy immune-depleting therapies.